Frequency, reasons, correlates and predictors of missed nursing care in Turkey: A multi‐hospital cross‐sectional study. Issue 5 (16th March 2022) - Taskiran Eskici, Gulcan; Baykal, Ulku
Abstract: Aim: We aimed to examine the frequency, reasons, correlates and predictors of missed nursing care in Turkey. Methods: This descriptive and cross‐sectional study sample consisted of 1310 nurses working in inpatient units of 10 public, university and private hospitals in Istanbul. Data were collected using the Nursing Teamwork Survey‐Turkish and the MISSCARE Survey‐Turkish between February and June 2019. Descriptive analysis, parametric comparative analysis, correlational analysis and regression analysis were used to analyse the data. Results: The total occurrence of missed nursing care was 2.93 (on a scale of 1.00–4.00), which differed across 21 nursing care elements. The most frequently missed care was turning patients every 2 hours. Multiple regression analysis determined that nurses' tenure in the profession, patient–nurse ratio, days absent in the last 3 months and nursing teamwork significantly affected missed nursing care. Nursing teamwork alone accounted for 23.6% of the variance in missed nursing care. Conclusions: The level of missed nursing care was found to be high, and labour resources issues were the most important reason. Nurse professionals should apply interventions to improve nurses' work environment factors such as patient–nurse ratio and nursing teamwork to reduce the incidence of missed nursing care. Summary statement: What is already known about this topic? Missed nursing care is a globally common patient safety issue that threatens quality nursing care. Although there are many studies from different countries in the international literature on missed nursing care, studies on this subject in Turkey have been limited. What this paper adds? Missed nursing care correlated with age, tenure in hospital, tenure in unit, weekly work hours, satisfied in current position, satisfaction with being a nurse, satisfaction with salary, technological, educational and career opportunities of the hospital, satisfaction with the level of teamwork in the unit, and satisfaction with support of first‐line nurse manager. Nurses' tenure in the profession, patient–nurse ratios, days absent in the last 3 months and nursing teamwork significantly affected missed nursing care. The implications of this paper: Strategies to improve nurses' work environment characteristics, especially teamwork, should be organized to prevent or reduce missed nursing care. Hospital administrators and nurse managers should address levels of missed nursing care through balancing patient–nurse ratios, providing adequate human and material resources, increasing technological, educational, and career opportunities of hospitals, meeting nurses' needs and providing support and performing activities to reduce absenteeism.